2021
DOI: 10.1002/ece3.8285
|View full text |Cite
|
Sign up to set email alerts
|

Soil resource availability is much more important than soil resource heterogeneity in determining the species diversity and abundance of karst plant communities

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…Therefore, growing plants that can maintain soil fertility and establish a good microbial community is one way to prevent or reduce the degradation of arable land in karst areas and increase yield. However, for degraded karst ecosystems, studies mainly investigated changes in (1) soil quality (Zhang et al, 2021); (2) plant diversity (Liu et al, 2021); and (3) hydrological characteristics (Liu, Jiang, et al, 2022). For degraded karst ecosystems, the effect of human disturbance on other ecological components, such as different plant‐type communities of soil microbes and their relationships with environmental factors in the cultivated land, has not been well‐studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, growing plants that can maintain soil fertility and establish a good microbial community is one way to prevent or reduce the degradation of arable land in karst areas and increase yield. However, for degraded karst ecosystems, studies mainly investigated changes in (1) soil quality (Zhang et al, 2021); (2) plant diversity (Liu et al, 2021); and (3) hydrological characteristics (Liu, Jiang, et al, 2022). For degraded karst ecosystems, the effect of human disturbance on other ecological components, such as different plant‐type communities of soil microbes and their relationships with environmental factors in the cultivated land, has not been well‐studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that different types and shapes of microplastics may differentially affect plant growth because they may differ in phytotoxicity ( Dong et al., 2020 ; Pignattelli et al., 2020 ; Li et al., 2022 ) and in the effect on soil physio-chemical properties and soil microbial communities such as soil microbial activity and mycorrhizal binding in plant roots ( de Souza Machado et al., 2019 ; Rillig et al., 2019 ; Lozano and Rillig, 2020 ; Lozano et al., 2021 ; Zhao et al., 2021 ). The promoted evenness of soil heterogeneity in the horizontal distribution of microplastics may be due to the increased microhabitat diversity, as observed in studies examining effects of soil heterogeneity in other factors ( Liu et al., 2021 ; Helbach et al., 2022 ). However, it is unclear what resulted in the decreased species evenness in the soil with the heterogeneous distribution of EPS, which seemed not to be related to the difference in the patch-level responses of individual plant species ( Figure S1 , Table S5 ).…”
Section: Discussionmentioning
confidence: 93%
“…Compared to animals, our traitbased method appeared to work better when explaining support for abundant-centre patterns in plants, suggesting that other processes that remain untested here may contribute to the unexplained variation in observed abundance-distance patterns. These biotic and abiotic processes may include, but are not limited to, interspecific interactions (Goldberg and Barton 1992;Robertson 1996), spatiotemporal patterns in resource availability (Theodose and Bowman 1997;Liu et al 2021), climate and environmental suitability (Maitra et al 2022), geodiversity (Bailey et al 2018), and pressures from human activities (Lepczyk et al 2008;Jesse et al 2018). Our focus on species' dispersal capabilities responded to recent research (Santini et al 2018;Feng & Qiao 2022) which found dispersal to be one of the most important processes driving abundance-distance patterns at a global scale.…”
Section: Discussionmentioning
confidence: 99%